Caracterização através de análise química da escultura portuguesa sobre madeira de produção erudita e de produção popular da época barroca - Barata, Carolina (2016)
Making use of several analytical techniques, four erudite and four popular Portuguese baroque wooden sculptures were studied. The materials and techniques employed were identified and the relationship between their artistic quality and the materials used was investigated. In general, the pigments were common at the time, but one pigment discovered in the beginning of the 18th century and two rare arsenic pigments were also identified. In popular sculptures cost-saving was detected, particularly concerning the gold leaf. Regarding some technical procedures identified, recommendations found in historical documents did not seem to have been entirely followed, neither in erudite nor in popular sculptures.